INTERNAL DISORDER PATTERN AMONG CHILDREN AND ADOLESCENTS WITH SPEECH DISORDERS - Khazova, Svetlana; Sevastyanova, Ulyana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The study explored general and specific characteristics of the internal disorder pattern among children and adolescents with speech impairments. The internal disorder pattern is considered an integrative construct that demonstrates the perception and attitude of a person to his disorder and includes components: physical (assessment of their physical activity and attributes), sensitive (complex of feelings associated with a disorder), cognitive (knowledge about disorder causes, symptoms and their health limited opportunities), motivational (motives and its possible change caused by a disorder) and emotional (individual’s attitude to their disorder). The internal disorder pattern affects I-concept development and is significant for an individual’s successful social adaptation. The sample consisted of 88 participants – preschoolers (т=20), elementary school children (т=33) and adolescents (n=35). The results show the differences of the cognitive and affective components (p≤0,05). The formation of the internal picture of the defect makes a greater contribution to the problems of adaptation in children of primary school age compared to other age groups.